Effects of pulmonary rehabilitation on airway microbiota detected in the saliva of patients with COPD - Andrade, Bárbara Cristiana Pereira de (2019)
Chronic Obstructive Pulmonary Disease (COPD) is the third leading cause of mortality worldwide. Pulmonary Rehabilitation (PR), a comprehensive intervention that includes several components, one of which is exercise training, is the most cost-effective therapy for patients with COPD. Exercise training increases ventilation and oxygen uptake, which most likely influences airway microbiota. However, how this influence occurs is still poorly understood. This study aimed to study the impact of RR on pulmonary microbiota in patients with COPD by exploring the microbial composition, alpha and beta diversity. Sociodemographic, anthropometric, clinical and saliva samples (once a month) were collected from a group of patients over a period of ~ 9 months (~ 3 months before RR, 3 months during RR and 3 months after RR) and in another patient group for a period of 6 months (without RR). Saliva microbiota was characterized by 16s rRNA sequencing and analyzed using the QIIME2 pipeline. Twenty-five patients with COPD who underwent PR (19♂, 73±6y, FEV1pp 48±15) and 5 patients who never had PR (5♂, 75±6y, FEV1pp 48±13) participated in the study. A significant increase of Proteobacteria phylum and Neisseria genus from pre-PR to PR period was observed. LEfSe showed that pre-PR comparing with during PR, samples’ microbiotas are enriched in the genera Pseudomonas and Shingomonas and during PR samples’ microbiotas are enriched in Neisseria and Alloscardovia. When comparing the periods during PR with post-PR, LEfSe pointed Granulicatella and Acinetobacter as being enriched during PR period and Staphylococcus, Selenomonas and Pasteurellaceae family as being enriched in the post-PR period. Comparing pre-PR with post-PR periods, LEfSe pointed Granulicatella, Sphingomonas, Pseudomonas and Enhydrobacter as being enriched in the pre-PR period and Pasteurellaceae family as being enriched in the post-PR period. No significant differences were observed in alfa diversity when comparing the different periods. LME model showed that time has a significant impact in alfa-diversity and that the interaction between PR and time passage are mainly contributing for microbiota dynamics, in non-phylogenetic metrics. PERMANOVA showed that microbiota does not converge per period. In conclusion, PR does not seem to significantly alter the structure of microbiota (alpha diversity) but changes composition. In general, alpha diversity is influenced by the passage of time and not by PR. Beta-diversity analyses showed that there is no microbiota convergence during or after PR. In non-phylogenetic metrics, microbiota dissimilarity is impacted by interaction between PR and time passage.